Advanced Neuromonitoring and Imaging in Pediatric Traumatic Brain Injury - Stuart H. Friess; Todd J. Kilbaugh; Jimmy W. Huh (Critical Care Research and Practice)
While the cornerstone of monitoring following severe pediatric traumatic brain injury is serial neurologic examinations, vital signs, and intracranial pressure monitoring, additional techniques may provide useful insight into early detection of evolving brain injury. This paper provides an overview of recent advances in neuromonitoring, neuroimaging, and biomarker analysis of pediatric patients following traumatic brain injury.